Dynamic renoscintigraphy in cardiology and cardiac surgery - V.Yu. Kundin; I.V. Noverko; A.G. Mazur (Кардіохірургія та інтервенційна кардіологія)
The article presents the possibilities of radionuclide research of kidney function and morphology in cardiology using dynamic renoscintigraphy. Variants of study modification, indications, conditions and methods of carrying out scintigraphy are presented. Calculations of the main features of quantitative and temporal parameters of renal function, steps of the the processing of diagnostic information and its practical significance are provided. Renographic curves are analyzed in normal and abnormal kidney function. The article presents the pharmacological test with captopril used for evaluation of renal function in hypertension, features of such test in cardiology practice and its evaluation in different clinical situations. Advantages of dynamic renoscintigraphy over other urinary system imaging methods are shown.